Retromer Controls Planar Polarity Protein Levels and Asymmetric Localization at Intercellular Junctions - Strutt, Helen (Curr Biol, 2019)
The coordinated polarization of cells in the plane of a tissue, termed planar polarity, is a characteristic feature of epithelial tissues [1]. In the fly wing, trichome positioning is dependent on the core planar polarity proteins adopting asymmetric subcellular localizations at apical junctions, where they form intercellular complexes that link neighboring cells [1, 2, 3]. Specifically, the seven-pass transmembrane protein Frizzled and the cytoplasmic proteins Dishevelled and Diego localize to distal cell ends, the four-pass transmembrane protein Strabismus and the cytoplasmic protein Prickle localize proximally, and the seven-pass transmembrane spanning atypical cadherin Flamingo localizes both proximally and distally. To establish asymmetry, these core proteins are sorted from an initially uniform distribution; however, the mechanisms underlying this polarized trafficking remain poorly understood. Here, we describe the identification of retromer, a master controller of endosomal recycling [4, 5, 6], as a key component regulating core planar polarity protein localization in Drosophila. Through generation of mutants, we verify that loss of the retromer-associated Snx27 cargo adaptor, but notably not components of the Wash complex, reduces junctional levels of the core proteins Flamingo and Strabismus in the developing wing. We establish that Snx27 directly associates with Flamingo via its C-terminal PDZ binding motif, and we show that Snx27 is essential for normal Flamingo trafficking. We conclude that Wash-independent retromer function and the Snx27 cargo adaptor are important components in the endosomal recycling of Flamingo and Strabismus back to the plasma membrane and thus contribute to the establishment and maintenance of planar polarization.